(untitled) (Anclajes, 2022)
Looking at the compositional dimension of publications allows us to think about the relationships between literature and periodicals based on what the magazines expose and offer to the view/read and how they do it. Journals can be considered as intermediaries (Chartier) with specific modes of display (Rogers). Within the framework of these definitions, I propose to study the relationships between journals, literature and publishing practices in Samuel Glusberg’s journal Babel, published between 1921 and 1929, trying to pinpoint two distinct moments that corresponded to particular strategies of material organization of the publication that impacted and shaped the very notion of literature within the journal. During the first stage, as Revista de Arte y Crítica (n.° 1 – n.° 12), it articulated what it considered artistic practices through the mediation of a critical word about what it circumscribed within the term art. During the second period, as Revista de Bibliografía (n.° 13 – n.° 29), there was a clear change in the architecture of Babel; this change was linked to a movement of editorial specialization that imbued the journal with the same name, founded in 1922, and brought it closer to the catalogue form.